Online World Language Instruction Training and Assessment : An Ecological Approach - King Ramirez, Carmen; Wermers, James E.; Lafford, Barbara A. (Book collections on Project MUSE., 2021)
"US World Languages (WL) departments have been rapidly growing their online language programs. Coupled with the widespread implementation of virtual teaching in response to COVID-19, there has been a tremendous increase in online teaching and learning of languages. Even with many resources and preparation time, there are few resources assessment tools that evaluate the quality of online content and instruction. This book will fill the gap. King Ramirez, Lafford, and Wermers provide critical pedagogical approach to CALL teacher education (CTE) training and assessment of online language instructors by combining best practices with assessment tools to provide support and guidance to WL teachers and administrators to help build successful and strong online programs. They walk readers through the process, taking a holisitic approach to address all facets of learning and environment, including equitable and fair trainings. The authors provide extensive rubrics and tools to help improve WL teaching online and explain important considerations in adapting them to each program's needs. In addition, there will be free worksheets on the press website (press.georgetown.edu) to further lead readers to success"--